2021
DOI: 10.3390/md19060292
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Vaccinia Virus Expressing White-Spotted Charr Lectin Regulates Antiviral Response in Tumor Cells and Inhibits Tumor Growth In Vitro and In Vivo

Abstract: Oncolytic vaccina virus (oncoVV) used for cancer therapy has progressed in recent years. Here, a gene encoding white-spotted charr lectin (WCL) was inserted into an oncoVV vector to form an oncoVV-WCL recombinant virus. OncoVV-WCL induced higher levels of apoptosis and cytotoxicity, and replicated faster than control virus in cancer cells. OncoVV-WCL promoted IRF-3 transcriptional activity to induce higher levels of type I interferons (IFNs) and blocked the IFN-induced antiviral response by inhibiting the acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…The results showed that oncoVV-AVL exhibited an efficient antitumor effect with a unique immunomodulatory mechanism, that is, inducing the production of type I IFNs while suppressing the ISREmediated viral defense response to promote self-replication. Our results support the idea that arming vaccinia virus with marine lectin can not only enhance the persistence of viral replication but also promote therapeutic efficacy [22].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The results showed that oncoVV-AVL exhibited an efficient antitumor effect with a unique immunomodulatory mechanism, that is, inducing the production of type I IFNs while suppressing the ISREmediated viral defense response to promote self-replication. Our results support the idea that arming vaccinia virus with marine lectin can not only enhance the persistence of viral replication but also promote therapeutic efficacy [22].…”
Section: Discussionsupporting
confidence: 86%
“…The volume of tumor was measured and recorded every five days. Tumor volume (V) was calculated as: V = (length × width 2 )/2 [22].…”
Section: In Vivo Tumor Formation Experiments In Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, blocking the IFN-induced antiviral response is achieved through two pathways. On the one hand, OncoVV-WCL can inhibit the activity of IFN stimulatory response element (ISRE), and on the other hand, inhibition of JAK-STAT signaling pathway by OncoVV-WCL limits ISG expression ( 160 ). By these means, the virus can avoid elimination by the antiviral pathway and thus exert a normal lytic effect ( 160 ).…”
Section: Molecular Mechanisms By Which Different Oncolytic Virus Ther...mentioning
confidence: 99%
“…Wang, Zhou, Liu et al demonstrate the construction of a oncoVV-WCL recombinant virus, obtained though the insertion of the white-spotted charr lectin (WCL) gene into an oncolytic vaccinia virus (oncoVV) vector [ 8 ]. WCL is a rhamnose-binding lectin belonging to the SUEL-type lectin family, identified from white-spotted Charr ( Salvelinus leucomaenis ) eggs based on its primary structure.…”
mentioning
confidence: 99%